2020
DOI: 10.3390/cryst10090841
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Dependent Reversible Structural and Magnetic Transformation between Two Ladder Compounds

Abstract: We report reversible structural transformation that occurs in two ladder compounds: Cu2CO3(ClO4)2(NH3)6 (1) and Cu2CO3(ClO4)2(NH3)5(H2O) (2), when they are exposed to gaseous vapors. The ladder structures of both 1 and 2 consist of two Cu2+ ions and one CO32− ion. In 1, the Cu2+ ions are coordinated by three NH3 molecules on each side, while those in 2 are coordinated by three NH3 molecules on one side, and two NH3 molecules and one H2O molecule on the other side. We demonstrated reversible transformation of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…• Manabe et al reported reversible structural and magnetic transformations in inorganic ladder compounds; these transformations are dependent on the gasphase chemical species absorbed in single crystals [23].…”
mentioning
confidence: 99%
“…• Manabe et al reported reversible structural and magnetic transformations in inorganic ladder compounds; these transformations are dependent on the gasphase chemical species absorbed in single crystals [23].…”
mentioning
confidence: 99%